2010
DOI: 10.5171/2010.698412
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contribute To Slow Internet Adoption in Omani Private Sector Organizations

Abstract: The study explores the reasons for the slow adoption of Internet technologies in Omani private sector organizations. A survey questionnaire was used to collect data from 60 private Omani organizations. One of the main factors for not adopting internet technologies was that internet is not relevant to their business. An insufficient level of demand for purchasing through Internet, lack of availability of skilled employees and security concerns were cited as the main factors for not adopting Internet in Omani or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The literature has widely discussed issues related to EB adoption in the developed counties but lesser attention was given to the developing counties in relation to these issues. Furthermore, results of this study revealed that in general, Omani manufacturing companies are still in the early stages of adopting EB and they might prefer face-to-face communication with their supply chain members including e-business efforts and firm performance their customers, similar to what has generally been reported by previous EB studies conducted in the same region (Al-Gharbi and Ashraf, 2010;Sabhi, 2012). The ongoing efforts to upgrade the Internet infrastructure in Oman has encouraged many businesses and individuals to accept the idea of adopting EB but still more efforts might be needed to promote more adoption of these global market requirements.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The literature has widely discussed issues related to EB adoption in the developed counties but lesser attention was given to the developing counties in relation to these issues. Furthermore, results of this study revealed that in general, Omani manufacturing companies are still in the early stages of adopting EB and they might prefer face-to-face communication with their supply chain members including e-business efforts and firm performance their customers, similar to what has generally been reported by previous EB studies conducted in the same region (Al-Gharbi and Ashraf, 2010;Sabhi, 2012). The ongoing efforts to upgrade the Internet infrastructure in Oman has encouraged many businesses and individuals to accept the idea of adopting EB but still more efforts might be needed to promote more adoption of these global market requirements.…”
Section: Discussionsupporting
confidence: 82%
“…With the huge infrastructure development, ongoing government support and increasing number of Internet users, Oman and most of its neighbouring Gulf Corporate Council (GCC) countries can be recognised as good players in the development of EB activities, and as a very good market for EB applications, especially those related to information communication technologies (ICTs). Despite the increasing importance of EB around the world and the ongoing efforts of most of the GCC countries including Oman in developing infrastructures needed for successful adoption of EB practices in these countries, very limited efforts have been made as yet to empirically investigate the linkages between EB practices and performance of the manufacturing sectors in GCC countries in general and in the Omani context in particular (Al-Gharbi and Ashraf, 2010;Sabhi, 2012;Goyal et al, 2019). By studying EB practices and performance in Oman, this research will contribute significantly to the existing knowledge about this region and will provide more realistic and practical implications for managers and decision-makers in the Sultanate of Oman and other similar contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have examined various leadership styles, with numerous studies conducted on leadership style models developed many years ago, such as contingency, behavioural, trait and situational theories. Nevertheless, few research studies have been conducted on how leadership leads to the adoption of technologies such as e-commerce in organisations (Al-Junaibi et al, 2022;Vivian, Aidi, & Ram, 2018;Ahmed, 2017;Yan & Yan, 2013;Al-Gharbi, & Ashrafi, 2010). Many previous studies and literature on SMEs and e-commerce adoption tend to focus on factors that influence adoption decisions or differentiate users from non-users (Scupola 2014).…”
Section: Introductionmentioning
confidence: 99%